Peran Perbankan Syariah bagi Masyarakat Kecil sebagai Upaya dalam Mengatasi Kemiskinan di Indonesia - Rizal Fahlevi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
The role of sharia banking in overcoming poverty in Indonesia has started toincrease but not yet optimal. This is due to the fact that the contracts are stillcommercial-oriented, short-term and sensitive to interest movements and dominatethe non-profit sharing (murabaha) contracts on the practice of sharia banking whichcan only be enjoyed by a handful of middle and upper class people with income ratioin Above average, not yet optimal innovative products sharia banking that can touchthe majority of the poor where in the aggregate most of t he Muslims. The purpose ofthis study is to analyze the not optimal role of sharia banking in overcoming povertyby exploring what should be done to improve the role of Islamic banking for thesmall community. The analytical method used is qualitative. While the analyticaltool used is descriptive and literature study is a very important source. Therecommendation of research result indicates that the need to optimize bankingproducts in small and medium enterprises, the need to optimize the role of shariabanking as a model of social intermediation, it is necessary to establish an effectiveselling price murabaha. The need for (benchmark) Islamic finance, the need tooptimize the real role of sharia economy.